2009
DOI: 10.1021/jp900336e
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale, Noncurling, and Free-Standing Crystallized TiO2 Nanotube Arrays for Dye-Sensitized Solar Cells

Abstract: Large-area noncurling crystallized free-standing TiO 2 nanotube (TNT) arrays have been fabricated by a twostep anodization process. These free-standing crystallized TNT arrays can be easily transferred to fluorinedoped tin oxide glass substrates without any crack. Furthermore, the investigation of these crystallized freestanding TNT arrays in dye-sensitized solar cells (DSSCs) was carried out and showed a roughly 100% enhanced conversion efficiency compared with that of the TNT array on a Ti substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
158
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(161 citation statements)
references
References 35 publications
1
158
1
1
Order By: Relevance
“…242 It is believed that TiO 2 nanotubes could be superior to nanorods or nanowires because of the availability of inner as well as outer walls of tubes for dye adsorption. [225][226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244] In 2007, Zhu et al reported the dynamics of electron transport and recombination in DSSCs incorporating oriented TiO 2 nanotube (NT) arrays. 229 The NT arrays consisted of closely packed NTs, several microns in length, with typical wall thickness and inter-tube spacing of 8-10 nm and pore diameters of about 30 nm, as shown in Fig.…”
Section: Selected Recent Progressmentioning
confidence: 99%
“…242 It is believed that TiO 2 nanotubes could be superior to nanorods or nanowires because of the availability of inner as well as outer walls of tubes for dye adsorption. [225][226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244] In 2007, Zhu et al reported the dynamics of electron transport and recombination in DSSCs incorporating oriented TiO 2 nanotube (NT) arrays. 229 The NT arrays consisted of closely packed NTs, several microns in length, with typical wall thickness and inter-tube spacing of 8-10 nm and pore diameters of about 30 nm, as shown in Fig.…”
Section: Selected Recent Progressmentioning
confidence: 99%
“…The TNTs grown on the Ti metallic foils only allow back side illumination because of the opaqueness of the Ti metal. With back side illumination, the counter electrodes (CEs) should be as transparent as possible, otherwise they will reflect light and the iodine-based electrolytes will absorb photons, which reduces the level of light harvesting significantly [10,11]. Recently, to overcome this problem, front side-illuminated TNTs have been recognized by transferring free-standing TNTs to transparent fluorine-doped tin oxides (FTOs) substrates [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…With back side illumination, the counter electrodes (CEs) should be as transparent as possible, otherwise they will reflect light and the iodine-based electrolytes will absorb photons, which reduces the level of light harvesting significantly [10,11]. Recently, to overcome this problem, front side-illuminated TNTs have been recognized by transferring free-standing TNTs to transparent fluorine-doped tin oxides (FTOs) substrates [11][12][13]. In this article, two types of TiO 2 nanotubes arrays (TNTs) were synthesized: the conventional TNT (Type I TNT) fabricated by one-step electrochemical anodization and the nanoporous-layer-covered TNT (Type II TNT) fabricated by two-step electrochemical anodization.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been reported to accomplish successful detachment of the tube arrays from the metal substrate, and the transferred TiO 2 nanotube layers have been explored in DSSCs in various configurations (tube bottom up/down and open/close tube bottom) [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%